The Influence of Technological Progress on The Preservation of National Customs and Behavior Patterns - Azhar, Annisa; Aryanti, Silvia Dwi; Rohmah, Sintia Ainur; Adiningsih, Wahana (Sahabat Publikasi, 2025)
The research in this journal is focus on analyzing the impact of technological developments on the preservation of national customs and behavior patterns with the aim of understanding how technological developments can affect customs and behavior of people at the national level. This research method uses a qualitative approach by collecting sources on the topics discussed such as journals and websites from the internet. The results of the study show that technological developments have a significant impact on the preservation of customs and behavior patterns that affect them in several aspects. The influence of technological developments on the preservation of the nation's customs and behaviors includes adjustments, alterations, or even fading. Ease of access to information and global interaction with technology has led to changes in people's customs and behavior. However, technology can be used as a powerful tool to strengthen the preservation of the nation's customs and behavior through the wider dissemination of information.